2024
DOI: 10.1021/jacsau.4c00005
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Redox Noninnocence of Pentane-2,4-dione Bis(S-methylisothiosemicarbazone) in Cobalt Complexes and Their Application in Wacker-Type Oxidation

Vincent Porte,
Miljan N. M. Milunovic,
Ulrich Knof
et al.

Abstract: Cobalt complexes with multiproton- and multielectron-responsive ligands are of interest for challenging catalytic transformations. The chemical and redox noninnocence of pentane-2,4-dione bis­(S-methylisothiosemicarbazone) (PBIT) in a series of cobalt complexes has been studied by a range of methods, including spectroscopy [UV–vis, NMR, electron paramagnetic resonance (EPR), X-ray absorption spectroscopy (XAS)], cyclic voltammetry, X-ray diffraction, and density functional theory (DFT) calculations. Two comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 140 publications
0
1
0
Order By: Relevance
“…18,24–26 Methodologies using first-row transition metals relied on using hydrosilanes as a hydrogen source leading to the oxidation of olefins with a marked Markovnikov selectivity. 18,27–34 On the other hand, the Lei group demonstrated that the photochemical single-electron oxidation of olefins, in the presence of a cobalt catalyst, leads to the correspondent carbonyl derivate with anti-Markovnikov selectivity (Scheme 1A). 24 With this in mind, we designed a mechanistically distinct Wacker-type oxidation of styrene derivates, capitalizing on phenacyl intermediates' absorbance properties.…”
Section: Introductionmentioning
confidence: 99%
“…18,24–26 Methodologies using first-row transition metals relied on using hydrosilanes as a hydrogen source leading to the oxidation of olefins with a marked Markovnikov selectivity. 18,27–34 On the other hand, the Lei group demonstrated that the photochemical single-electron oxidation of olefins, in the presence of a cobalt catalyst, leads to the correspondent carbonyl derivate with anti-Markovnikov selectivity (Scheme 1A). 24 With this in mind, we designed a mechanistically distinct Wacker-type oxidation of styrene derivates, capitalizing on phenacyl intermediates' absorbance properties.…”
Section: Introductionmentioning
confidence: 99%